2021
DOI: 10.1021/acs.inorgchem.0c03102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Study, and Application of Pd(II) Hydrazone Complexes as the Emissive Components of Single-Layer Light-Emitting Electrochemical Cells

Abstract: For the first time, square planar Pd­(II) complexes of hydrazone ligands have been investigated as the emissive components of light-emitting electrochemical cells (LECs). The neutral transition metal complex, [Pd­(L1)2]·2CH3OH (1), (HL1 = (E)-N′-(phenyl­(pyridin-2-yl)­methylene)­isonicotinhydrazide), was prepared and structurally characterized. Complex 1 displays quasireversible redox properties and is emissive at room temperature in solution with a λmax of 590 nm. As a result, it was subsequently employed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…The shift of the CN bonds to higher wavenumbers (1593–1585 in free ligands and 1617–1605 cm −1 in 1–3 ) demonstrates the coordination of pyridine rings (CN bond) to the Cu( ii ) ion. 30 In the vibration spectrum of compound 3, the broad band at 3393 cm −1 is attributed to the alcoholic and acidic O–H, and the strong band at 1761 cm −1 is related to the CO group of 2-hydroxyacetic acid. 31 Although these compounds were successfully synthesized by the reaction of corresponding ligands and copper salts, this process is a time-consuming process by considering the long time required for the synthesis of the ligands.…”
Section: Resultsmentioning
confidence: 98%
“…The shift of the CN bonds to higher wavenumbers (1593–1585 in free ligands and 1617–1605 cm −1 in 1–3 ) demonstrates the coordination of pyridine rings (CN bond) to the Cu( ii ) ion. 30 In the vibration spectrum of compound 3, the broad band at 3393 cm −1 is attributed to the alcoholic and acidic O–H, and the strong band at 1761 cm −1 is related to the CO group of 2-hydroxyacetic acid. 31 Although these compounds were successfully synthesized by the reaction of corresponding ligands and copper salts, this process is a time-consuming process by considering the long time required for the synthesis of the ligands.…”
Section: Resultsmentioning
confidence: 98%
“…The destructive effect of ionic additives on LEC lifetime has also been reported in the literature. , Recently, in the same approach, we used a protonated palladium complex containing a pyridinium moiety as an orange emitter in an LEC. The results showed that the protonated complex exhibited greater maximum luminescence than the nonprotonated complex in an LEC, while the EQE of an LEC based on a protonated emitter decreased significantly …”
Section: Resultsmentioning
confidence: 99%
“…The strong bands at 1638 and 1601 cm −1 in the FT‐IR spectrum of ligand (see Figure S1) are due to the amidic C=O and imine C=N functionalities, respectively. [ 22 ] The band of naphtholic OH group is observed as a broad band at 3391 cm −1 , which is overlapped with the bands at 3309 and 3244 cm −1 . These bands (3309 and 3244 cm −1 ) are assigned to amidic NH and free amine (−NH 2 ) groups.…”
Section: Resultsmentioning
confidence: 99%
“…The strong band at 1606 cm −1 in the FT‐IR spectrum of 1 (Figure S5) is due to the C=N stretching frequency of the hydrazone ligand. [ 22 ] Due to the coordination of ligand (H 2 L) in the iminol form, the amidic C=O band is eliminated and a new band is observed at 1622 cm −1 , which is related to the formation of –C=N–N=C– unit. [ 24 ] The bands at 3229 and 3340 cm −1 can be attributed to the free NH 2 group and are overlapped with the broad OH band located at about 3424 cm −1 .…”
Section: Resultsmentioning
confidence: 99%